Skala Zaufania do Przełożonego jako narzędzie do mierzenia zaufania do menedżerów - Wnuk, Marcin (Humaniora. Czasopismo Internetowe, 2020)
Background: The aim of the study was operationalizing trust in supervisor concept and assesses the psychometric properties of the tool using to measure this construct. Material and Methods: Subjects were 804 employees from different organizations. The following measures were used: Perceived Supervisor Support Scale, Perceived Stress at Work Questionnaire, Grattitude Towards Organization Scale, Organizational Loyalty Scale and 2 measures – regarding intention to leave and job satisfaction. Results: Confirmed very good psychometric properties of Trust in Supervisor Scale. Factor analysis statistically confirmed the two dimensional structure of this measure inclusive benevolence and integrity factor containing 12 items and abilities as well as competences containing 8 items. The reliability of the Trust in Supervisor Scale was confirmed using the α-Cronbach coefficient. The proof of the theoretical validity of this measure are its positive correlations with job satisfaction, loyalty and gratitude towards the organization as well as its negative relationships with the intend to quit organization and the level of stress. Conclusions: The obtained results confirm that the Trust in Supervisor Scale has a very good psychometric properties and may be used in practice to explore trust in mangers in organizations in Poland.